2021
DOI: 10.3389/fphar.2021.651599
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic Shock Applied After Perinatal Asphyxia Prevents Retinal Damage in Rats

Abstract: Perinatal asphyxia (PA) can cause retinopathy and different degrees of visual loss, including total blindness. In a rat model of PA, we have previously shown a protective effect of hypothermia on the retina when applied simultaneously with the hypoxic insult. In the present work, we evaluated the possible protective effect of hypothermia on the retina of PA rats when applied immediately after delivery. Four experimental groups were studied: Rats born naturally as controls (CTL), animals that were exposed to PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 49 publications
(64 reference statements)
2
6
0
3
Order By: Relevance
“…Instead, we targetted hypothermia to the injured pre-chiasmatic ON according to early transcriptomic changes in ischemia, inflammation, and metabolism pathways ( Figure 4 ). Previous study also indicated that hypothermia-induced elevated expression of cold-shock proteins may contribute to neuronal protection ( Rey-Funes et al, 2021 ; Larrayoz et al, 2016 ,) especially in the mild hypothermia range ( Tong et al, 2013 ; Zhu et al, 2016 ). Hypothermic treatment may directly prevent neuronal degeneration, and early treatment is necessary to alleviate further progression of neural damage after optic nerve injury ( Rey-Funes et al, 2017 ) as well as after other CNS trauma ( Markgraf et al, 2001 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Instead, we targetted hypothermia to the injured pre-chiasmatic ON according to early transcriptomic changes in ischemia, inflammation, and metabolism pathways ( Figure 4 ). Previous study also indicated that hypothermia-induced elevated expression of cold-shock proteins may contribute to neuronal protection ( Rey-Funes et al, 2021 ; Larrayoz et al, 2016 ,) especially in the mild hypothermia range ( Tong et al, 2013 ; Zhu et al, 2016 ). Hypothermic treatment may directly prevent neuronal degeneration, and early treatment is necessary to alleviate further progression of neural damage after optic nerve injury ( Rey-Funes et al, 2017 ) as well as after other CNS trauma ( Markgraf et al, 2001 ).…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, the current local treatment did not achieve functional recovery of the eye-to-brain pathway, and its long-term therapeutic effect is unclear. In contrast, while cold treatment at the injury site has the advantages of being local, precisely controlled, and deeper hypothermia, previous articles that applied cold treatment to the whole animal also obtained positive results in vision preservation ( Rey-Funes et al, 2017 ; Rey-Funes et al, 2021 ), indicating that cold treatment applied to the retina or to the whole animal may be further explored and perhaps in conjunction with local hypothermia. Another limitation of this study is a small sample size in each therapeutic group.…”
Section: Discussionmentioning
confidence: 98%
“…Los resultados presentados tienen cierta similitud con lo publicado previamente por nuestro laboratorio en los estudios de retina, donde se observa el incremento de la CIRBP y la RBM3 en sus diversas capas a las 12, 24 y 48 h posteriores a la aplicación de la hipotermia. 10,27 En resumen, la presencia de la CIRBP en la médula espinal a nivel torácico (T8-T9-T10) se encuentra tanto en animales a temperatura ambiente como en animales expuestos a hipotermia, su expresión es significativamente mayor en los animales expuestos a hipotermia con una cinética de expresión y localización diferente entre las 12, 24 y 48 h posteriores a la intervención.…”
Section: Discussionunclassified
“…[18][19][20][21][22] Aún no se han develado por completo los procesos intrínsecos por los cuales el frío produce protección tisular. Sin embargo, se ha descrito la expresión de diferentes proteínas inducibles por frío, tales como la proteína de unión al ARN inducible por frío (cold-inducible RNA binding protein, CIRBP) y la proteína 3 del motivo de unión al ARN (RNA binding motif protein 3, RBM3) 7,9,11,[23][24][25][26][27][28] que podrían ser de gran relevancia.…”
Section: Introductionunclassified
“…Therapeutic hypothermia consists in reducing the body (or a particular organ´s) temperature to obtain medical benefits. Its usefulness has been proven in managing several pathologies such as neonatal asphyxia ( Cornette 2012 ; Rey-Funes et al, 2021 ), coronary artery bypass surgery ( Sirvinskas et al, 2014 ), neurodegeneration after cardiopulmonary resuscitation ( Arrich et al, 2012 ), stroke ( Ikeda et al, 2012 ; Minnerup et al, 2012 ; Lyden et al, 2014 ; Rogers et al, 2014 ), or ocular traumatisms ( Rey-Funes et al, 2017 ), among others. However, despite these accomplishments, the clinical implications of therapeutic hypothermia in central nervous system (CNS) injury remain controversial.…”
Section: Introductionmentioning
confidence: 99%